Social experience vs. social technology in enhancing the intention to use social commerce: a case study of Indonesia. Issue 3 (8th June 2020) - Handarkho, Yonathan Dri
Abstract : Purpose: This study proposed a theoretical model to understand user intention to use social commerce (SC) of an emerging market based on social experience and social technology. The SC scope was limited to the third-party Social Network Sites utilized by the vendor to establish social interaction and communication with and among the customer about commercial activity. Design/methodology/approach: A total of 750 Indonesian respondents were used to examine the research model using online and offline self-administered questionnaires. Findings: The findings from the final model showed Perceived Enjoyment from the social technology factor has the most substantial direct effect on behavior intention in SC followed by the direct effect of Perceived Usefulness, the indirect effect of content quality, and social presence. Meanwhile, from social experience, the perceived herd was found to have a strong immediate effect on intention, followed by the direct effect of emotional support and indirect effect of subjective norms. Originality/value: Concerning SC study in emerging markets, the previous research also explored user intention from social and technical aspects, especially with the focus on consumer's desire to purchase. Meanwhile, the focus of this study was to investigate the determinant of social interaction intention by engaging in the SC community, which differs from prior research.